The Role of Digital Marketing in Enhancing Market Reach and Customer Engagement in Nepalese Enterprises - Adhikari, Shankar Nath; Molla, Nasiruddin (Journal of Advanced Academic Research, 2024)
This study investigates the impact of digital marketing on customer engagement and market reach among enterprises in Kathmandu, Nepal. Conducted from January to March 2023, the research employed a mixed-method approach, utilizing a structured questionnaire including Likert scale distributed through convenience sampling to 423 respondents, including business owners and their customers. The data analysis was conducted using Smart-PLS (version 4) and SPSS (version 26), incorporating various statistical techniques, including frequency distribution, percentages, mean values, standard deviation, path coefficient analysis, t-statistics, and R-squared metrics. The study focused on key digital marketing parameters, including social media presence, digital marketing budget, content quality and strategy, website optimization, and the use of data analytics. Findings indicate that these digital marketing practices significantly enhance both market reach and customer engagement, resulting in improved business performance. However, many business owners reported challenges due to limited knowledge and resources, which hinder their ability to fully leverage these strategies. Customer insights further validate the effectiveness of digital marketing, highlighting good engagement levels while pointing out areas for improvement. The research underscores the necessity for targeted digital marketing training programs for business owners in Kathmandu, emphasizing essential skills such as customer behavior analysis, content creation, and performance measurement. Such initiatives could lead to enhanced market presence, increased customer retention, and overall business growth. The findings provide valuable recommendations for business owners and their customers to strengthen the digital marketing capabilities of enterprises in Nepal.